Analysis of influencing factors voluntary disclosure in sector companies various industries listed on the indonesian stock exchange 2006-2008 period - Dimas Bayu Erlangga (Indonesia Auditing Research Journal, 2022)
This research has a purpose to find out the factors which can affect the voluntary disclosure in the annual report. The factors examined in this research are firm size, leverage, profitability, percentage of public share and age of companies. The samples consist of 18 miscellaneous industries from 2006 through 2008 and are still listed on IDX. The object of this research was the firm's annual report during the 2006-2008 period and the data analysis was treated as panel data. The statistical method used to test on the research hypothesis is multiple regression. The result shows the factors that affect significantly the voluntary disclosure are leverage, profitability and age of companies. The other factors like firm size and percentage of public share have no significant relation. However, the other results of this research show that firm size, leverage, profitability, percentage of public share and age of companies simultaneously had a significant effect on voluntary disclosure.